2006
DOI: 10.1259/bjr/25049149
|View full text |Cite
|
Sign up to set email alerts
|

Breast screening: PERFORMS identifies key mammographic training needs

Abstract: The UK Breast Screening Programme has recently expanded the age range for invitation in the prevalent round to 70 years. In contrast, fewer radiologists now choose to specialise in the area of breast cancer screening. In response to this depletion in film-reading personnel, an increasing number of radiographers have been trained as advanced practitioners in order to film-read alongside the current radiologists. As part of the quality assurance programme for the National Health Service Breast Screening Programm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 8 publications
4
25
2
Order By: Relevance
“…The percentage of cases correctly classified by the participants (n=8) indicated that they made significantly less errors on abnormal (64% correct response) as compared to the normal cases (36.4% correct response). Similar results are also observed with in the PERFORMS scheme using normal sized mammographic film images and this may be exacerbated here by the small screen size [15]. Even so, this problem is not peculiar to PDAs and tends to result in false positive responses.…”
Section: Discussionsupporting
confidence: 82%
“…The percentage of cases correctly classified by the participants (n=8) indicated that they made significantly less errors on abnormal (64% correct response) as compared to the normal cases (36.4% correct response). Similar results are also observed with in the PERFORMS scheme using normal sized mammographic film images and this may be exacerbated here by the small screen size [15]. Even so, this problem is not peculiar to PDAs and tends to result in false positive responses.…”
Section: Discussionsupporting
confidence: 82%
“…Such interactive training ideally should be undertaken on the digital clinical workstations themselves but this is not always possible due to time and cost constraints as the workstations are primarily *y.chen3@lboro.ac.uk used for the clinical practice of screening. In the UK a national annual self assessment scheme can help identify the training needs of particular groups or individuals 4 which can then lead to the development of particular training sets of cases 5 .…”
Section: Introductionmentioning
confidence: 99%
“…All films were single read, with the exception of patients in family history screening, for whom the second read was undertaken by a breast clinician with more than 10 years' mammographic experience and who satisfied Royal College of Radiologist guidelines for screening breast radiology practice [16]. In addition, all film readers regularly participated in breast audit and undertook the Personal Performance in Mammographic Screening (PERFORMS) test to evaluate individual performance [17].…”
Section: Methodsmentioning
confidence: 99%